Nab-paclitaxel versus solvent-based paclitaxel in patients with previously treated advanced gastric cancer (ABSOLUTE): an open-label, randomised, non-inferiority, phase 3 trial. (April 2017) - Shitara, Kohei; Takashima, Atsuo; Fujitani, Kazumasa; Koeda, Keisuke; Hara, Hiroki; Nakayama, Norisuke; Hironaka, Shuichi; Nishikawa, Kazuhiro; Makari, Yoichi; Amagai, Kenji; Ueda, Shinya; Yoshida, Kazuhiro; et al.
Summary: Background: Weekly administration of solvent-based paclitaxel is one of the standard second-line chemotherapy regimens for advanced gastric cancer. Nanoparticle albumin-bound paclitaxel (nab-paclitaxel) was developed to improve the solubility of paclitaxel and does not need premedication to avoid infusion-related reactions associated with solvent-based paclitaxel. Additionally, higher doses of nab-paclitaxel can be administered over a shorter infusion time and at higher drug concentrations compared with solvent-based paclitaxel. We aimed to investigate the efficacy and safety of nab-paclitaxel versus solvent-based paclitaxel in patients with previously treated advanced gastric cancer. Methods: We did a randomised, open-label, non-inferiority, phase 3 trial at 72 institutions in Japan. Patients aged 20 years or older with advanced gastric adenocarcinoma refractory to a fluoropyrimidine-containing first-line chemotherapy regimen, with progressive disease or a relapse fewer than 24 weeks after the final dose of adjuvant chemotherapy were randomly assigned (1:1:1) to receive intravenous nab-paclitaxel (260 mg/m 2 ) every 3 weeks (on day 1 of a 21-day cycle), weekly nab-paclitaxel (100 mg/m 2, on days 1, 8, and 15 of a 28-day cycle), or weekly solvent-based paclitaxel (80 mg/m 2, on days 1, 8, and 15 of a 28-day cycle). Randomisation was done with the minimisation method, with stratification for previous use of docetaxel, presence of peritoneal metastases, and Eastern Cooperative Oncology Group (ECOG) performance status. The primary endpoint was overall survival in the full analysis set, which included all randomly assigned patients who received at least one dose of study drug, with a non-inferiority margin of 1·25 for the hazard ratio. This trial is registered with Japan Pharmaceutical Information Center Clinical Trial, number JapicCTI-132059, and has been completed. Findings: Between March 13, 2013, and May 14, 2015, 741 patients were randomly assigned to nab-paclitaxel every 3 weeks (n=247), weekly nab-paclitaxel (n=246), or weekly solvent-based paclitaxel (n=248). Median follow-up for overall survival was 9·99 months (IQR 6·05–15·05). Median overall survival was 10·3 months (95% CI 8·7–11·4) in the group that received in the nab-paclitaxel every 3 weeks, 11·1 months (9·9–13·0) in the weekly nab-paclitaxel group, and 10·9 months (9·4–11·8) in the weekly solvent-based paclitaxel group. Weekly nab-paclitaxel was non-inferior to weekly solvent-based paclitaxel (hazard ratio 0·97, 97·5% CI 0·76–1·23; non-inferiority one-sided p=0·0085), whereas nab-paclitaxel every 3 weeks was not non-inferior to solvent-based paclitaxel (1·06, 95% CI 0·87–1·31; non-inferiority one-sided p=0·062). The main grade 3 or worse adverse drug reactions were neutropenia (158 [65%] of 244 patients in the group that received nab-paclitaxel every 3 weeks vs 99 [41%] of 241 patients in the weekly nab-paclitaxel group vs 71 [29%] of 243 patients in the weekly solvent-based paclitaxel group), peripheral sensory neuropathy (49 [20%] vs six [2%] vs six [2%]), and febrile neutropenia (30 [12%] vs seven [3%] vs two [1%]). Hypersensitivity reactions were less frequent with nab-paclitaxel every 3 weeks (two [1%] patients) and weekly nab-paclitaxel (three [1%] patients) than with weekly solvent-based paclitaxel (13 [5%] patients). Four treatment-related deaths were reported overall (pneumonia in one patient in the group that received nab-paclitaxel every 3 weeks, febrile neutropenia/pneumonia in one patient, and septic shock in one patient in the weekly nab-paclitaxel group, and respiratory disease/interstitial lung disease in one patient in the weekly solvent-based paclitaxel group). Interpretation: As the trial showed that weekly nab-paclitaxel was non-inferior to weekly solvent-based paclitaxel in terms of overall survival, the advantages of the nab-paclitaxel formulation make it a potential regimen for second-line treatment of gastric cancer. Funding: Taiho Pharmaceutical.